Afasia: una perspectiva clínica - González V., Rafael; Hornauer-Hughes, Andrea (Revista Hospital Clínico Universidad de Chile, 2014)
Language is a complex and dynamic system of conventional signs that results from the functioning of different brain areas located mainly in the left hemisphere. Clinical evaluation of aphasia implicates the examination of oral and written language. Aphasia is an acquired language disorders due to a brain damage that affect all modalities: oral expression, auditory comprehension, reading and writing. Various types of aphasias can be induced, each with well defined clinical characteristics that can be correlated with specific areas of the brain. The prognosis depends mainly on the etiology, size of the lesion, type of aphasia and itsseverity. Treatment objectives include: satisfying the communicational needs of the patient, and achieving psychosocial adaptation of the subject and his family. Both objectives improve the quality of life of our patients.